2021
DOI: 10.3389/fendo.2021.735554
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Managing Pediatric Diabetes and Other Endocrine Disorders During the COVID-19 Pandemic: Results From an International Cross-Sectional Electronic Survey

Abstract: BackgroundFrequency, dimensions, management, and outcomes of the COVID-19 pandemic in children with endocrine disorders and diabetes were assessed.MethodsA cross-sectional electronic survey was distributed to the global network of endocrine societies. Respondents’ professional and practice profiles, clinic sizes, their country of practice, and the impact of COVID-19 on endocrine diseases were investigated.ResultsRespondents from 131 pediatric endocrine centers in 51 countries across all continents completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 48 publications
1
19
1
1
Order By: Relevance
“…There were also no significant differences in glycaemic control parameters or in the incidence and severity of DKA between the pre-COVID and COVID populations in our study. This stands in opposition to some reports of an increased incidence of DKA during the pandemic [17,18]. Additionally, although without statistical significance, we observed that the highest blood glucose level readings at admission were all recorded in the pre-COVID group, and the number of DKA incidents in the pre-pandemic population was nearly double that of the COVID group.…”
Section: Discussioncontrasting
confidence: 99%
“…There were also no significant differences in glycaemic control parameters or in the incidence and severity of DKA between the pre-COVID and COVID populations in our study. This stands in opposition to some reports of an increased incidence of DKA during the pandemic [17,18]. Additionally, although without statistical significance, we observed that the highest blood glucose level readings at admission were all recorded in the pre-COVID group, and the number of DKA incidents in the pre-pandemic population was nearly double that of the COVID group.…”
Section: Discussioncontrasting
confidence: 99%
“…An increase in the incidence of DKA was reported by 17.6% of the surveyed centers during the first few months of the pandemic, and that was slightly higher than what was reported by Elbarbary et al 11 for which 15% of their responders reported an increased incidence of DKA. However, that incidence was lower than another international cross-sectional electronic survey conducted later by Elbarbary et al 14 in which 44% of their respondents reported increased diabetic ketoacidosis episodes in newly diagnosed cases and 30% in established cases. Similarly, Alaqeel et al 15 studied the impact of COVID-19 pandemic lockdown on the incidence of new-onset T1DM and ketoacidosis among Saudi children.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, a regular outpatient follow-up of children and adolescents with obesity, which often requires closely-timed visits to be effective, has been made difficult by the above-mentioned restrictions. Elbarbary et al., in an International Cross-Sectional Electronic Survey distributed to the global network of endocrine societies, estimated a 41.5% delay in obesity diagnosis and a perceived worsening in obesity management in 83% of cases due to the COVID-19 pandemic ( 21 ). Our study showed that, although outpatient follow-up would not appear to have been compromised, its efficacy was lower in obese patients followed during the pandemic period compared with those followed in the pre-pandemic period, due to the increase of an unhealthy lifestyle characterized by a significant reduction in physical activity and increased time spent watching TV, playing video games and using electronic devices, and by an increased consumption of junk food.…”
Section: Discussionmentioning
confidence: 99%